PENGARUH PREMI ASURANSI TERHADAP PEMENUHAN KEWAJIBAN PERPAJAKAN - Dinda Fahira Lubis; Ainil Harnita Simanullang; Dara Lutfiah Nur; Dini Vientiany (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research aims to investigate the effect of insurance premiums on fulfilling tax obligations in Indonesia. Insurance premiums are costs incurred by companies or individuals to protect themselves from certain risks, while tax obligations are obligations that must be fulfilled in accordance with the legal provisions of the country concerned. This study uses primary data from insurance companies and secondary data related to tax regulations in Indonesia. The analytical method used is regression to test the relationship between insurance premiums and the level of fulfillment of tax obligations. It is hoped that the results of this research will provide deeper insight into the factors that influence the fulfillment of tax obligations in the insurance sector, as well as relevant policy implications.